Evaluating the Impact of Digital Support on Parental Stress in Swedish Child Health Care: Results From an Intervention Study - Lotha Valan; Ulf Isaksson; Asa Hörnsten; Asa Carlsund (International Journal of Pediatrics)
Conclusion: Despite a limited outcome change, the results showed a tendency to benefit some parents. Our findings suggest that further evaluation, possibly with other more suitable measurements or questionnaires, an extended intervention period, and a larger sample, is necessary to understand the implications of these results fully.